2007
DOI: 10.1177/0018726707083476
|View full text |Cite
|
Sign up to set email alerts
|

Overlapping effects: Path dependence and path generation in management and organization in Russia

Abstract: An important contribution to our understanding of management transformation in post-socialist societies has been made by new institutionalism. The strength of this approach derives from its critique of normative models based on neo-classical economics, which has tended towards institutional and management voluntarism. It has been able to grasp complexity in societies undergoing structural change, stressing that path dependence in property, political and social structures helps to define business organization. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
19
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(19 citation statements)
references
References 30 publications
0
19
0
Order By: Relevance
“…Authors such as Whitley (1999) suggest that the data available on post‐communist economies, particularly related to CEECs, indicate that they need to be studied and treated separately; such reasoning is in line with the work of Mayrhofer and Brewster (1996), who suggested that national and regional differences hold back the development of a pan‐European HR model and that it is the ‘pre‐existing’ national systems and historical contexts that hold this integration back (Tregaskis and Brewster, 2006). Furthermore, what makes emerging European countries unique is that, in general, despite varying degrees of similarity, their individual economic performance and size differ substantially (Schwartz and McCann, 2007); these substantive differences have been brought to the forefront during the recent economic downturn with some of these countries being more susceptible to what has been occurring around them.…”
Section: Hr Research In Emerging European Markets: Developments and Dmentioning
confidence: 99%
“…Authors such as Whitley (1999) suggest that the data available on post‐communist economies, particularly related to CEECs, indicate that they need to be studied and treated separately; such reasoning is in line with the work of Mayrhofer and Brewster (1996), who suggested that national and regional differences hold back the development of a pan‐European HR model and that it is the ‘pre‐existing’ national systems and historical contexts that hold this integration back (Tregaskis and Brewster, 2006). Furthermore, what makes emerging European countries unique is that, in general, despite varying degrees of similarity, their individual economic performance and size differ substantially (Schwartz and McCann, 2007); these substantive differences have been brought to the forefront during the recent economic downturn with some of these countries being more susceptible to what has been occurring around them.…”
Section: Hr Research In Emerging European Markets: Developments and Dmentioning
confidence: 99%
“…Even though the countries constituting the SEE region of Europe have some similarities, their size, political importance and economic performance differ dramatically (Schwartz and McCann 2007). This is likely to affect the nature of IR development in each one of them.…”
Section: Understanding the See Context Of Industrial Relationsmentioning
confidence: 99%
“…This suggests that historical factors in Eastern Europe may impinge on the ability for MNCs to introduce Western style practices into their Eastern European subsidiaries (Bandelj 2003;Brown 2007;Hausner et al 1995;Schwartz and McCann 2007;Stark 1998). In their examination of the initial post-transformation period of the early 1990s, Hausner et al argued that the collapse of socialism did not lead to an institutional vacuum that could simply be filled with Western management Global Consistency Versus Local Responsiveness 47 concepts and practices.…”
Section: Strategic International Human Resource Managementmentioning
confidence: 99%